Acute kidney injury due to rhabdomyolysis-associated gangrenousmyositis - Daher, E. F.; Lima, R. S.A.; Silva Júnior, G. B.; Almeida, et al., J. P.C. (Acta Biomedica Atenei Parmensis, 2008)
Rhabdomyolysis is associated with infectious diseases in approximately 5% of cases and acute kidney injury occurs in 33-50% of cases. Gangrenous myositis is a deep seated infection of the subcutaneous and muscular tissues. We report the case of an 18 year-old man who was admitted to the emergency room with leg pain, fever, nausea, vomiting and oliguria.  Physical examination showed moderate dehydration, peripheral cyanosis and skin necrosis with severe myalgia and no subcutaneous gas. Laboratory findings at admission were: serum urea 111 mg/dL, creatinine 1.3 mg/dL, potassium 6.3 mEq/L, creatine kinase (CK) 112,452 IU/L, aspartate amino transaminase (AST) 1116 IU/L, alanine amino transaminase (ALT) 1841 IU/L, pH 7.31, bicarbonate (HCO3) 11 mEq/L and lactate 4.3 mmol/L. Emergency hemodyalisis was started, and antibiotics were given due to high suspicion for bacterial infection. The patient developed respiratory insufficiency and septic shock needing mechanical ventilation and vasoactive drugs.  He presented spontaneous gangrenous myositis in both legs and in his left arm. After 26 sessions of hemodialysis, partial recovery of renal function was observed.  He was discharged from the ICU after 38 days, still with leg pain. Acute kidney injury due to rhabdomyolysis should be considered as a possible complication of gangrenous myositis.